Raising the Potential of the Domestically Oriented Sector in Germany - Eid, André (OECD Publishing, 2015)
Germany's manufacturing sector, which plays an important role for exports, has been performing well over the past decade in terms of labour productivity growth and international competitiveness. However, the services sector has had much slower growth rates. Competition often appears to be hindered by protection of incumbents. Reforming and deregulating the domestically oriented sectors, including network industries, crafts and professional services would release hidden growth potential and prove beneficial to the economy as a whole. It could also help strengthen domestic demand and reduce dependence on exports. This Working Paper relates to the 2014 Economic Survey of Germany (www.oecd.org/eco/surveys/economic-survey-germany.htm)
Keywords: Economics; Germany